2021
DOI: 10.3389/fimmu.2021.676181
|View full text |Cite
|
Sign up to set email alerts
|

The Role of V-Domain Ig Suppressor of T Cell Activation (VISTA) in Cancer Therapy: Lessons Learned and the Road Ahead

Abstract: Immune checkpoints (ICs) have pivotal roles in regulating immune responses. The inhibitory ICs in the tumor microenvironment (TME) have been implicated in the immune evasion of tumoral cells. Therefore, identifying and targeting these inhibitory ICs might be critical for eliminating tumoral cells. V-domain immunoglobulin suppressor of T cell activation (VISTA) is a novel inhibitory IC that is expressed on myeloid cells, lymphoid cells, and tumoral cells; therefore, VISTA can substantially regulate innate and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 86 publications
(144 reference statements)
0
28
0
Order By: Relevance
“…Although containing a similar molecular sequence with the B7 superfamily, VISTA does not possess ITIM/ITAM (immunoreceptor tyrosine-based activation motif). VISTA is expressed on myeloid cells (e.g., monocytes, conventional DCs, macrophages, and circulating granulocytes), T cells, Tregs, and TILs ( Hosseinkhani et al, 2021 ). There are increasing pieces of evidence showing VISTA as a regulatory immune checkpoint.…”
Section: Biology Of Immune Checkpoint Proteinsmentioning
confidence: 99%
“…Although containing a similar molecular sequence with the B7 superfamily, VISTA does not possess ITIM/ITAM (immunoreceptor tyrosine-based activation motif). VISTA is expressed on myeloid cells (e.g., monocytes, conventional DCs, macrophages, and circulating granulocytes), T cells, Tregs, and TILs ( Hosseinkhani et al, 2021 ). There are increasing pieces of evidence showing VISTA as a regulatory immune checkpoint.…”
Section: Biology Of Immune Checkpoint Proteinsmentioning
confidence: 99%
“…Multiple cell types can express VSIR, such as cancer cells, neutrophils, monocytes, macrophages, dendritic cells (D.C.s), and T cells in humans and mice ( Flies et al, 2011 ; Lines et al, 2014 ). Previous studies have found that VSIR is widely involved in various physiological and pathological processes, including regulating peripheral tolerance, inducing T cell activation and differentiation, and mediating tumor immunity ( ElTanbouly et al, 2019 ; Hosseinkhani et al, 2021 ). Thus, growing evidence indicated that VSIR might be a promising target for tumor immunotherapeutic intervention in the TME.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mAbs targeting immune checkpoints enhance T cells' antitumor immune response and improve antitumor defense [7,13]. Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), programmed death 1 (PD-1), and its ligand (PD-L1), as well as the B7 family of immune checkpoints, could be considered to be the main immunotherapy targets to inhibit tumor growth in a variety of cancers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%